2013
DOI: 10.4238/2013.april.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of the humphead wrasse, Cheilinus undulatus

Abstract: ABSTRACT. The humphead wrasse (Cheilinus undulatus) is a large coral fish that has become threatened due to habitat loss and fishing pressure. We sequenced the mitochondrial genome of C. undulatus, using a normal PCR method. The complete mtDNA sequence encoded 13 protein genes, 22 tRNA genes and 2 rRNA genes. It was found to be 16,613 bp in length and had an overall H-strand base compositions of 27.3 for A, 30.9 for C, 16.8 for G, and 25.0% for T. Compared with the sequences of 8 other members of the family La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Among those genes, 2 rRNAs, 12 PCGs, and 15 tRNAs are encoded on the plus strand (H strand) and the remaining are encoded on the minus strand (L strand). The organization and location of the mitochondrial genome of H. Hartzfeldii are in accordance with the pattern observed in the mitogenomes of other typical Labridae (Qi et al 2013). The overall base composition of the mitogenome of H. hartzfeldii is biased towards A þ T content at 52.9%.…”
Section: Halichoeres Hartzfeldii; Mitogenome; Phylogenetic Analysissupporting
confidence: 81%
“…Among those genes, 2 rRNAs, 12 PCGs, and 15 tRNAs are encoded on the plus strand (H strand) and the remaining are encoded on the minus strand (L strand). The organization and location of the mitochondrial genome of H. Hartzfeldii are in accordance with the pattern observed in the mitogenomes of other typical Labridae (Qi et al 2013). The overall base composition of the mitogenome of H. hartzfeldii is biased towards A þ T content at 52.9%.…”
Section: Halichoeres Hartzfeldii; Mitogenome; Phylogenetic Analysissupporting
confidence: 81%
“…The first step was to obtain the sequences of the 16S rRNA, COI and Cyt b genes by PCR with universal primers [ 5 , 22 , 23 ], and the sequence gaps in these mitochondrial genes can then be obtained by the specific primers designed based on the known sequences listed above; the resulting fragments of the PCR products, obtained with only seven sets of PCR primers, are shorter than 3000 bp and can be sequenced by Sanger sequencing. Compared to other sequencing methods, such as PCR amplification with multiple PCR primer pairs (> 15) [ 21 , 24 ] and next-generation sequencing [ 13 , 19 ], our strategy can avoid nonspecific amplification or other problems resulting from sequence assembly.…”
Section: Discussionmentioning
confidence: 99%
“…We cloned the complete mitochondrial genome of I. trivittatus and found that the gene order of the mtDNA was as commonly described [ 21 ]. The gene length is similar to that of other wrasses; for example, the 12S rRNA gene lengths are 947 bp to 956 bp, and the 16S rRNA gene lengths are from 1684 bp to 1702 bp in the known mtDNA of eight species of wrasses (GenBank accession listed in Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for species of conservation concern that are not well protected, as is the case for this species over extensive areas, identification of key larval source areas and habitat may support more effective management and protection of populations should these reach much-reduced levels (Cabral et al 2016). To date, although microsatellite loci (Hu et al 2013) and whole mitochondrial genomes (Qi et al 2013, Matthew et al 2018 including the control region (Indriatmoko et al 2016) have been characterized, there has been no population genetic analysis of C. undulatus. Our goal in this paper is to provide the first estimates of phylogeographic and population genetic structure of the Humphead wrasse across much its range and, thus, inform strategies for managing fisheries sustainably, including conserving genetic diversity in a time of rapid environmental change and increasing exploitation pressure (Rocha et al 2007, Carvalho et al 2017.…”
Section: Introductionmentioning
confidence: 99%